PERAN MEDIASI KEPUASAN KERJA ATAS PENGARUH PENGALAMAN KERJA DAN MOTIVASI BERPRESTASI TERHADAP PRODUKTIVITAS KERJA (Studi Pegawai Badan Kesatuan Bangsa dan Politik Kota Pasuruan) - Erwin Krissanto; Sodik Sodik; Kuncoro Kuncoro (Bajang Institute, 2022)
This study aims to obtain empirical evidence of the ability of work experience and achievement motivation in encouraging increased work productivity, either directly or through job satisfaction mediation.This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 35 employees of the National Unity and Political Institution of Pasuruan City.Empirical evidence shows that both work experience is able to motivate achievement, both are able to encourage an increase in job satisfaction, but only achievement motivation is able to strongly encourage an increase in work productivity, while work experience has a weak effect. The mediating role of job satisfaction is proven to be strong, because although the direct relationship between work experience and productivity is weak, if you neglect mediation, the effect will be strong. This finding is supported by the descriptive of the four variables, all of which received high responses, including work requiring previous work experience, proficient and quality results, thorough and correct work performance assessment, liking team work, adequate facilities, salary according to workload, trying to meet or exceed targets, as well as following the work program